Preclinical Testing of Antihuman CD28 Fab′ Antibody in a Novel Nonhuman Primate Small Animal Rodent Model of Xenogenic Graft-Versus-Host Disease. Issue 12 (December 2016) - Hippen, Keli L.; Watkins, Benjamin; Tkachev, Victor; Lemire, Amanda M.; Lehnen, Charles; Riddle, Megan J.; Singh, Karnail; Panoskaltsis-Mortari, Angela; Vanhove, Bernard; Tolar, Jakub; Kean, Leslie S.; Blazar, Bruce R.
Abstract : Background: Graft-versus-host disease (GVHD) is a severe complication of hematopoietic stem cell transplantation. Current therapies to prevent alloreactive T cell activation largely cause generalized immunosuppression and may result in adverse drug, antileukemia and antipathogen responses. Recently, several immunomodulatory therapeutics have been developed that show efficacy in maintaining antileukemia responses while inhibiting GVHD in murine models. To analyze efficacy and better understand immunological tolerance, escape mechanisms, and side effects of clinical reagents, testing of species cross-reactive human agents in large animal GVHD models is critical. Methods: We have previously developed and refined a nonhuman primate (NHP) large animal GVHD model. However, this model is not readily amenable to semi-high throughput screening of candidate clinical reagents. Results: Here, we report a novel, optimized NHP xenogeneic GVHD (xeno-GVHD) small animal model that recapitulates many aspects of NHP and human GVHD. This model was validated using a clinically available blocking, monovalent anti-CD28 antibody (FR104) whose effects in a human xeno-GVHD rodent model are known. Conclusions: Because human-reactive reagents may not be fully cross-reactive or effective in vivo on NHP immune cells, this NHP xeno-GVHD model provides immunological insights and direct testing on NHP-induced GVHD before committing to the intensive NHP studies that are being increasingly used for detailed evaluation of new immune therapeutic strategies before human trials. Abstract : Hippen et al describe a novel nonhuman primate (NHP) xenogeneic GvHD model, using NSG mice as host for rhesus macaque peripheral blood mononuclear cells for the initial testing of human-reactive reagents for cross-reactivity prior to their use in NHP. Supplemental digital content is available in the text.